2017
DOI: 10.1101/136192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fitness, Physical Activity, and Cardiovascular Disease: Longitudinal and Genetic Analyses in the UK Biobank Study

Abstract: BackgroundExercise is inversely related with cardiovascular disease (CVD), but large-scale studies of incident CVD events are lacking. Moreover, little is known about genetic determinants of fitness and physical activity, and modifiable effects of exercise in individuals with elevated genetic risk of CVD. Finally, causal analyses of exercise traits are limited.MethodsWe estimated associations of grip strength, physical activity, and cardiorespiratory fitness with CVD and all-cause death in up to 502,635 indivi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 35 publications
4
56
0
Order By: Relevance
“…There has been limited work on PA and prevention of peripheral vascular diseases, particularly in general population cohorts, although existing data from patient samples are consistent with our findings [ 9 ]. Findings on PA and arrhythmias has been mixed; recent studies have shown associations between PA and physical fitness with reduced risk of atrial fibrillation [ 10 , 11 ] although others have suggested a non-linear pattern of results [ 12 , 13 ]. Our data showed an inverse association between PA and risk of stroke although we were unable to further sub-type cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been limited work on PA and prevention of peripheral vascular diseases, particularly in general population cohorts, although existing data from patient samples are consistent with our findings [ 9 ]. Findings on PA and arrhythmias has been mixed; recent studies have shown associations between PA and physical fitness with reduced risk of atrial fibrillation [ 10 , 11 ] although others have suggested a non-linear pattern of results [ 12 , 13 ]. Our data showed an inverse association between PA and risk of stroke although we were unable to further sub-type cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on coronary heart disease suggested a plateau in risk reduction at higher levels of PA. Nevertheless, recent work [ 11 ] comparing associations of self-reported and objective PA on CVD risk observed curvilinear and linear curves, respectively, suggesting that reporting bias might possibility explain increased risk in participants that mis-report very high PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…To help direct specific interventions for HF, a clear understanding of modifiable risk factors is important. It has been shown, for example, that hypertension, smoking, obesity, grip strength, cardiorespiratory fitness, physical activity levels, alcohol intake and diet quality are associated with HF incidence 7–9. However, whether these risk factors differ by sex has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…5, Supplementary Table 3e). Hand grip strength, a protective factor for cardiovascular casualty 40 , negatively associated with E. coli (Fig. 5).…”
Section: Resultsmentioning
confidence: 98%